A social determinants of health survey in an Appalachian East Tennessee Medical Center: Initial findings and correlations with physical and emotional states of health - Paul D. Terry; Gulsah Onar; Jennifer Ferris; Robert Eric Heidel; Nate Brophy; Kritika Thapa; Laylan Shali; Heidi Worth; Gayathri Kumar; Tracy Walker; Rajiv Dhand (PLoS ONE, 2025)
Background People living in Appalachia experience inequities in health outcomes that may result from social determinants of health (SDH) and consequent barriers to healthcare. Objective We aimed to assess SDH in our Appalachian patient population and examine associations between SDH and patients’ physical and emotional well-being. Methods We constructed and administered a SDH questionnaire in an urban medical center in Appalachian East Tennessee. Our survey included administration of the Short Form-36 (SF-36), which measures various domains of physical and emotional health. We used the SDH questionnaire to enumerate respondents’ barriers to health (a total barrier score), with a maximum of 47 barriers identified. Descriptive statistics were calculated as frequencies and percentages. Spearman’s and Pearson’s (r) correlations and hierarchical multiple regression models were used to quantify associations between the SDH barrier scores and SF-36 subscales. Results Our patients experienced substantial barriers to health (M = 11.61, SD = 5.10). SDH in our population included being underweight or overweight (BMI < 18.5 or ≥25; 71.2%), having a lower annual family income (<$50,000/year; 60.7%), and experiencing financial difficulty when seeking medical care (51.9%). Some differences in SDH prevalence according to sex were noted, such as a greater proportion of males (12.8%) than females (2.8%) having no health insurance. We observed statistically significant negative correlations between the SDH barriers score and all SF-36 subscales. After controlling for sex, age, and racial group, hierarchical multiple regression models showed a consistent negative relationship between SDH barrier score and all eight SF-36 subscales (B statistics ranged from −2.04 to −3.66). Conclusions Patients in our Appalachian population experience a high number of barriers to accessing healthcare that are negatively correlated with measures of physical and emotional well-being. To optimize patient care, assessment of patients’ physical and emotional health should complement the use of SDH questionnaires.